ENCOURAGING EMPLOYEE LOYALTY THROUGH JOB SATISFACTION - Berta Gracela Manalu; Kiki Farida Ferne (Universitas Efarina, 2025)
This study aims to analyze the influence of reward, transformational leadership, and work environment on employee loyalty with job satisfaction as a moderating variable at PT PLN (Persero) Customer Service Implementation Unit (UP3) Padangsidimpuan. The background of this research lies in the importance of maintaining employee loyalty to ensure the company's effectiveness and long-term sustainability. The population of this research consisted of all employees of PT PLN (Persero) UP3 Padangsidimpuan, with 86 respondents determined through a saturated sampling technique. The research method applied was quantitative, using a questionnaire as the instrument, and the data were analyzed using Partial Least Square (PLS). The findings revealed that reward has a positive and significant effect on employee loyalty. Transformational leadership also positively and significantly influences employee loyalty, while a conducive work environment enhances employee loyalty as well. Furthermore, job satisfaction functions as a moderating variable that strengthens the relationship between reward, transformational leadership, and work environment with employee loyalty. In conclusion, to improve employee loyalty, the company should provide fair rewards, implement transformational leadership, create a comfortable work environment, and ensure employee job satisfaction.